In situ characterization of crystallization and melting of soft, thermoresponsive microgels by small-angle X-ray scattering - Lapkin D. Dmitry; Mukharamova N. Nastasia; Assalauova D.; Dubinina S. Svetlana; Stellhorn J. R. Jens Rudiger; Westermeier F. Fabian; Lazarev S. V. Sergey Vladimirovich; Sprung M. Michael; Karg M. Matthias; Vartanyants I. A. Ivan; Meijer J.- M. Janne-Mieke (2022, 2022)
Title screen